FEMALE STUDENTS IN ENGINEERING Geology, Mining, and Petroleum Engineering Comparison - Lažnjak, Jasminka (Array, 1997)
Engineering professions generally went last decades through process of feminization, but not equally. The article is focused on one of the most male dominant profession - mining, geology and petroleum engineering (MGPE). This study will examine the percentage of female students and graduates from mining college and their achievement on undergraduate level in eleven years period. Data show a significant differences in female students enrollment among geology (35% women) and mining and petroleum engineering (14% women). The theoretical background in explanation why women are marginal group in MPE is based on two different approaches: technological determinism and social shaping of technology. The role of technology in altering of women position in society is significant. The social construction of technology thesis stresses social factors and interests of main actors which in this case include the reproduction of traditional value system and occupational segregation.